2006
DOI: 10.4319/lo.2006.51.1.0310
|View full text |Cite
|
Sign up to set email alerts
|

Coccolith strontium to calcium ratios in Emiliania huxleyi: The dependence on seawater strontium and calcium concentrations

Abstract: In recent studies the Sr/Ca ratio of coccolithophore calcite was used as a proxy for past coccolithophore growth and calcification rates. Since Sr and Ca concentrations in seawater have not remained constant through time, interpretation of Sr/Ca data from the coccolith-dominated sedimentary record requires knowledge about the incorporation of seawater Sr into coccolith calcite during coccolithogenesis. Here we show that Sr/Ca of Emiliania huxleyi coccoliths is linearly related to seawater Sr/Ca, meaning that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
98
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(106 citation statements)
references
References 39 publications
(80 reference statements)
8
98
0
Order By: Relevance
“…The results show that calcite crystals precipitated in the presence of large malonic acid concentrations show significant elongation along the c axis, and suggest that increasing malonate concentrations corresponded with increasing D Sr . Experiments with 10 À1 M malonic acid caused elevated D Sr comparable to that predicted for E. huxleyi coccolith calcite (Langer et al, 2006). …”
supporting
confidence: 59%
See 1 more Smart Citation
“…The results show that calcite crystals precipitated in the presence of large malonic acid concentrations show significant elongation along the c axis, and suggest that increasing malonate concentrations corresponded with increasing D Sr . Experiments with 10 À1 M malonic acid caused elevated D Sr comparable to that predicted for E. huxleyi coccolith calcite (Langer et al, 2006). …”
supporting
confidence: 59%
“…Carboxylic acids can affect calcite growth because of the similarity of the carboxyl (COO À ) group to the carbonate group (CO 3 2À ), allowing it to interact with Ca ions at the calcite surface through electrostatic attraction. The bidentate binding of the carboxyl groups of dicarboxylic acids to the calcite surface can effectively block acute kink sites (Mann et al, 1990) Langer et al (2006), inorganic calcite D Sr as expected from Tesoriero and Pankow (1996).…”
Section: Resultsmentioning
confidence: 99%
“…This, however, may no longer be the case for biologically mediated calcite precipitation. Organisms such as marine calcifying algae actively regulate Ca 2+ transport from the surrounding seawater to the site of calcification through cell physiological processes (Langer et al, 2006). In the highly controlled cell environment, r may differ significantly from the value in the bulk medium.…”
Section: Growth Rates and Solution Stoichiometrymentioning
confidence: 99%
“…The rate dependence of the Sr exchange coefficient as determined from inorganic calcite precipitation experiments was used to explain the apparent Sr exchange coefficients of biogenic calcite (Carpenter and Lohmann, 1992). The trace metal exchange coefficient of biogenic calcite is termed apparent exchange coefficient, because the trace metal to calcium ratio of the solution from which the crystal is precipitated (at the site of calcification within the organism) is unknown (Langer et al, 2006). A subsequent study, however, showed that kinetic effects are not appropriate to explain Sr partitioning in coccolithophores (Stoll et al, 2002).…”
Section: Introductionmentioning
confidence: 99%